Efectos de varios distanciamientos e híbridos sobre el rendimiento del cultivo de maíz (Zea mays L.), en el cantón Tosagua - Cevallos Zambrano, Francisco Sebastián (2022)
The present research work was carried out in the rainy season of the year 2021, in "Los Naranjos" community in Tosagua canton. It consisted of evaluating the effect of various distances and hybrids on the yield of the maize (Zea mays L.) crop. A completely randomized block experimental design (DBCA) was used with an A x B factorial arrangement, with 9 treatments and four treatments repetitions with a total of 36 experimental units. Three hybrids (Advanta 9139, Dass 3383 and Trueno) and three planting distances (0.80*0.20; 0.70*0.15; and 0.80*0.10) were studied. Data analysis was performed through ANOVA and mean separation through Tukey's test at 5% error probabilities. The variables evaluated were: plant emergence, days to male flowering, days to female flowering, number of plants in production, cob length (cm), cob diameter (cm), number of rows/cob, grain numbers /row, number of grain/cob, weight of cobs (g), yield per hectare (kg) and benefit/cost ratio. The results show that the Trueno hybrid obtained the highest percentage of emerged plants, but in the production components, the Advanta 9139 hybrid was superior in all the variables studied. In the distance and hybrid interaction, the sowing distance of 95,238 seeds ha-1 and the hybrid Advanta 9139 reached the highest yield (323 qq ha-1) and the best rate of return ($2,125).